Is there a link between overactive bladder and the metabolic syndrome in women? A systematic review of observational studies. Issue 2 (11th December 2014) - Bunn, F.; Kirby, M.; Pinkney, E.; Cardozo, L.; Chapple, C.; Chester, K.; Cruz, F.; Haab, F.; Kelleher, C.; Milsom, I.; Sievart, K. D.; Tubaro, A.; et al.
Summary Objectives To conduct a systematic review to determine whether there is an association between metabolic syndrome (MetS) and lower urinary tract symptoms (LUTS) or overactive bladder (OAB) in women. Methods We systematically reviewed English language observational studies on the effect of MetS (or component factors) on the presence of OAB or LUTS in women. We searched PubMed, Web of Science and The Cochrane Library with no date restrictions, checked reference lists and undertook citation searches in PubMed and Google Scholar. Studies were assessed for risk of bias. Because of heterogeneity, results were not pooled, but are reported narratively. Results Of 27 included studies, only three looked at the link between MetS and OAB. The rest looked at links between OAB and components of MetS such as obesity or insulin resistance (n = 10), between MetS and urinary symptoms (n = 3) and between urinary symptoms and components of MetS, such as obesity (n = 14). Evidence is currently limited, but it does suggest that there may be important links between MetS and OAB and components of MetS such as obesity. Conclusions The literature on MetS and OAB or LUTS in women is limited, and poor quality. However, the evidence available on obesity appears to support MetS as a contributor and predictor of LUTS in women. Many of the women with LUTS will be overweight and will have features of the MetS, if looked for. This provides not only an opportunity to encourage weight loss as an adjunct to therapy for the OAB symptoms but also a window of opportunity to address cardiovascular risk factors and prevent future cardiovascular morbidity and mortality.